Experimental Comparison of Encryption Algorithms On Smart Devices - Hakimi, Musawer; Frugh, Qurban Ali; Naseri, Mohammad Fahim (Universitas Pendidikan Nasional, 2024)
Now, the technological environments rely on a large number of users and devices interconnected in such a way as to be able to share information and exchange resources. For such reasons, security becomes of prime importance inside these networks. Especially, encryption algorithms widely used in smart metering systems form the very backbone of ensuring security. It is unique according to every single parameter: the level of security achieved, speed, operational complexity, length, and type of key used. A comparison of performance and throughput for the most used encryption algorithms, such as AES-128, AES-192, RC4, Blowfish, and ECDSA, is presented here. Such devices, for instance, smart meters, usually represent very resource-constrained computational capability, memory, and data transfer. For these reasons, the experiments investigate performance impacts of using different encryption algorithms on a smart meter environment in a scaled setup. Experiments were run on a laptop device and then downscaled according to the limitation characteristics of the smart meter target device. As for the scaling, it has been performed concerning key factors: CPU of the smart meter, RAM, and cache memory. Execution times of the encryption and decryption processes were measured, as well as the throughput of messages for various file sizes. Quantitative key results obtained included: RC4 with a throughput of 25.37 Kbytes/sec, whereas AES-128 has 4.87 Kbytes/sec, while in ECDSA-256 the performance is much lower: its verification throughput amounts to 0.0023 Kbytes/sec. The results showed significant variations in performance, speed, and throughput between these algorithms. Even considering small smart devices, the encryption and decryption processes yielded efficient throughputs. These findings underscore the importance of choosing the right encryption algorithm for smart meters, balancing both security requirements and resource limitations to ensure optimal performance.